Geomagnetic coast and other effects deduced from the new observatory at Visakhapatnam, India - Srivastava, B.J.; Abbas, Habiba; RamaGopal, T.; Rao, D.R.K.; Pathan, B.M. (My University, 2001)
Coastal effects observed in the long-period Sq Solar quist day ranges and short-period changes over 30min intervals during magnetic substorms (bays), as recorded at a new magnetic observatory at Visakhapatnam, on the east coast of India, during 1995 in the H, Z and D elements, are analysed and the preliminary results are discussed. The results are compared with those from Alibag and Hyderabad (located more or less at the same latitude) based on simultaneous 1995 records. Short-period induction vectors are computed and the arrows presented and discussed at the three locations. While the enhancement associated with close proximity to the coast in Sq(Z) at Alibag on the west coast compared to the central inland station of Hyderabad (enhancement of 17-37 per cent) is quite prominent in all three seasons of the year, at Visakhapatnam it is only marginally observed during the d-season. At bay frequencies, medium-sized induction arrows point towards the nearest deep-sea conductive body at both Alibag and Visakhapatnam, while it is towards the southeast with a considerably reduced magnitude at Hyderabad. These induction arrows and the effects on Sq(Z), Sq(H) and Sq(D) ranges are discussed in conjunction with the Parkinson arrows and Sq(Z), Sq(H) and Sq(D) ranges from Margao (west coast)-Dharwar-Bellary-Mahanandi-Chirala (east coast) at the latitude of the 16°N profile of an earlier array experiment, and the two are interpreted together.
Keywords: Channelling; Coast effect; Electromagnetic induction; Sq variation